Peculiarities of labor relations of state employees - Dmytro I. Sirokha, Mykola I. Inshyn,; Volodymyr M. Pavlichenko, Olena M. Ganechko, Olena A. Gubska, (Opción, 2020)
The purpose of this study is to identify and analyze the characteristics of labor relations in public service via the comparative analysis of legislation and doctrinal developments in the field under study. As a result, a feature of labor relations is the restriction of certain constitutional human rights in connection with civil service work. According to the results of the study, it can be concluded that relations in the field of labor of civil servants are included in the scope of labor law.